THE REPRESENTATION OF VIOLENCE ISSUE IN THE SELECTED SONG LYRICS AND VIDEO CLIPS OF SNOOP DOGG'S LATEST COMPILATION ALBUM - Lovina Fitriasari, - (2008)
The study was concerned with violence issue in Snoop Dogg's selected song lyrics and video clips. This study was aimed at finding out how the violence is constructed in Snoop Dogg's selected song lyrics and video clips. This issue had been chosen because it is the most shown issue that characterizes rap songs themes in hip hop culture. The song lyrics and video clips were analyzed with the framework of Van Dijk's macrostructure (topic) and superstructure (schema) Textual Analysis. The framework was used to find out the textual and visual evidence of violence indicators in the song lyrics and video clips. The macrostructure (topic) level raised several main topics that indicated violence, such as using vocative 'nigga' to call men and vocative 'bitch' to call women, partying with the presence of alcoholic drinks and illicit drugs, objectifying women, intimidating the foes, and doing implicit and explicit sex. The superstructure (schema) level depicted the topics in chronological order. Popular culture theory also framed the representation of violence. The textual and visual evidence of violence indicators in the song lyrics and video clips are constructed through popular culture, by putting Snoop's songs, daily life and controversies in publication and broadcasting them on radios, televisions and the internet. The publication spreads violent messages contained in the lyrics of rap songs and in the representation of the rapper's day by day life in the video clips.